A Disease Modification Effect of APOE E4 on the Association between Urinary Albumin Excretion and Cognition in Korean Adults. (30th October 2014) - Shin, Min-Ho; Kweon, Sun-Seog; Choi, Jin-Su; Lee, Young-Hoon; Nam, Hae-Sung; Park, Kyeong-Soo; Kim, Hee Nam; Oh, Sun-Young; Jeong, Seul-Ki
Abstract : Background . No previous study examined a disease modifying effect of APOE E 4 status on the association between the urinary albumin-to-creatinine ratio (UACR) and cognition. This study aimed to investigate whether APOE E 4 modified the association in Korean adults. Methods . We performed a cross-sectional study in adults aged 45 to 74 who were living in Namwon City, Republic of Korea. Cognitive function was measured with the Korean version of modified Mini-Mental State Examination (K-mMMSE) and cognitive impairment was defined as scores falling below the 25th percentile of the K-mMMSE according to age, sex, and educational attainments. Results . A total of 10, 190 participants (4006 men and 6184 women) were analyzed in the present study. Of these, 1698 subjects (16.7%) were APOE E 4 carriers. The UACR values were negatively associated with the K-mMMSE scores, even after adjusting for potential confounders including age, sex, education, and vascular risk factors. APOE E 4 modified the association significantly, resulting in a steeper decline of cognitive function with the increase in UACR in E 4 carriers ( P for interaction = 0.021). Conclusion . Higher UACR values were significantly associated with cognitive dysfunction in the general Korean population, with cognition in APOE E 4 carriers being more severely affected by increased UACR.